KEGIATAN PUBLIC RELATIONS SEBAGAI UPAYA PENGUATAN EKSISTENSI PERPUSTAKAAN - Komariah, Neneng; Rodiah, Saleha; Zaky Rakhmat, M. (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2018)
Library is an institution which provides selected information sources and services for people. The information sources available in library are selected and provided systematically makes people easy to find the needed information. However, some libraries suffer of lack of user so must be done library management for existance empowerment. This paper discuss implementation of “pencils” of public relations, it is a strategy in library empowerment conducted in Telkom University Open Library. Pencils of public relations is a strategy based on creating good relationship with relevant stakeholders which consists of publications, events, news, community involvement, identity tools, lobbying, and social investment. The research method used is descriptive qualitative and data collected by interview and focus group discussion. The results shows that the Telkom University Open Library has implemented “pencils” of public relations in strengthening its existence.